Review on the Occurrence of Mycotoxigenic Fungi in Dried Fruits and the Role of Stored-Product Insects - Dimitrios-Evangelos Miliordos; Georgia V. Baliota; Christos G. Athanassiou; Pantelis I. Natskoulis (Toxins, 2025)
Dried fruits, which are widely produced in different parts of the world, and, especially in the Mediterranean basin, are broadly known for their durability and their nutritional value. This is primarily due to their ability to be stored for long periods of time and their concentrated nutrient content. However, these fruits can be at risk of contamination by specific stored-product insects and various toxigenic fungal species at different stages of their production process, including cultivation, harvesting, processing, drying, and storage. As a result, the dried fruits that are consumed may contain mycotoxins, which pose a potential risk for human health. The risk is significant in both industrialized and developing nations, as climate change and inadequate sanitation practices contribute to the proliferation of mycotoxins in these commodities. It is worth noting that there are several factors that contribute to the production of mycotoxins, such as the type of fruit, geographical location, climatic conditions, harvest treatments, and storage management practices, with specialized insects, known as “stored-product insects”, playing a crucial role in this latter stage. Therefore, it is critically important to gain a comprehensive understanding of the interaction among insects, fungi, and mycotoxins to effectively mitigate this problem. In this review, the primary objective is to bridge the knowledge gap by consolidating data from various regions to gain a global perspective on this topic.